2019
DOI: 10.3892/ol.2019.11224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on the cognitive function of patients undergoing gastric cancer surgery by regulating the PI3K/AKT signaling pathway

Abstract: Effect of dexmedetomidine on the cognitive function of patients undergoing gastric cancer surgery by regulating the phosphoinositide 3-kinase (PI3K)/AKT signaling pathway was investigated. A total of 110 patients who were diagnosed and underwent radical gastrectomy in Ruijin Hospital North,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…DEX can effectively reduce the level of inflammatory factors in gastric cancer patients after operation. 24 Overall, these results suggested that DEX treatment can reduce perioperative OS and inflammation. miR-10a is abnormally expressed in many cancer types, such as colorectal cancer, breast cancer, and lung cancer.…”
Section: Discussionmentioning
confidence: 82%
“…DEX can effectively reduce the level of inflammatory factors in gastric cancer patients after operation. 24 Overall, these results suggested that DEX treatment can reduce perioperative OS and inflammation. miR-10a is abnormally expressed in many cancer types, such as colorectal cancer, breast cancer, and lung cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Random-effects model and fixed-effect model were used to synthesize the MMSE scores and the incidence of POCD at different time points after surgery in 7 RCTs to consider the effect of DEX on postoperative cognitive function comprehensively ( 17 , 28 , 31 – 33 , 35 , 36 ). As shown in Figure 5 , in digest tract tumor patients, DEX administration was associated with higher MMSE scores at 12h (SMD = 1.10, 95%CI: 0.74, 1.45), 24h (SMD = 0.85, 95%CI: 0.59, 1.11), 48h (SMD = 0.89, 95%CI: 0.50, 1.28) and 72h (SMD = 0.75, 95%CI: 0.38, 1.11) after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…DEX could resemble natural sleep, increase physiological sleep-wake cycle for ICU patients, and reduce the risk of delirium ( 16 ). DEX could also reduce the level of postoperative inflammatory factors through PI3K-Akt signaling ( 17 ), and inhibit cancer development through the upregulation of miR-185 and inactivation of SOX9-Wnt-β-catenin signaling ( 18 ). Moreover, there is growing evidence that DEX has a potential role during perioperative period for the prevention and alleviation of inflammation and immune dysfunction ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“… 148 Dexmedetomidine could effectively decrease the expression levels of postoperative serum inflammatory factors (including TNF-α, IL-6) in patients undergoing gastric cancer surgery, enhance postoperative cognitive function by regulating the PI3K-Akt signaling pathway, and promote recovery of postoperative cognitive function. 149 Its application in tumor surgery in children including in abdominal malignancy 150 shows improved postoperative analgesia with better overall analgesia compared with other agents such as fentanyl. The surgical application and consequent effects of dexmedetomidine are summarized in Figure 3 .…”
Section: Key Surgical Applicationsmentioning
confidence: 99%